2021
DOI: 10.31661/jbpe.v0i0.2104-1304
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Eye Lens Dose Estimate based on AAPM Report 293 in Head Computed Tomography

Abstract: Background: Estimation of eye lens dose is important in head computed tomography (CT) examination since the eye lens is a sensitive organ to ionizing radiation. Objective:The purpose of this study is to compare estimations of eye lens dose in head CT examinations using local size-specific dose estimate (SSDE) based on size-conversion factors of the American Association of Physicists in Medicine (AAPM) Report No. 293 with those based on size-conversion factors of the AAPM Report No. 220. Material and Methods:Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Values with P≤0.05 denoted statistical significance. The correlation interpretation (r) is as follows: |r|=1, perfect correlation; 0.8≤|r|<1, strong correlation; 0.5≤|r|<0.8, moderate correlation; 0.1≤|r|<0.5, weak correlation; and 0<|r|<0.1, the lowest correlation ( 16 ). Missing data were examined, and no patterns of missing data were identified.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Values with P≤0.05 denoted statistical significance. The correlation interpretation (r) is as follows: |r|=1, perfect correlation; 0.8≤|r|<1, strong correlation; 0.5≤|r|<0.8, moderate correlation; 0.1≤|r|<0.5, weak correlation; and 0<|r|<0.1, the lowest correlation ( 16 ). Missing data were examined, and no patterns of missing data were identified.…”
Section: Methodsmentioning
confidence: 99%
“…While this and AAPM report 220 rely on similar calculation methods, the conversion factor ( f ) of report 293 is more accurate because its calculation method is based on head phantom experiments that consider different ages and the Monte Carlo simulation ( 15 ). A recent study also showed the average local SSDE calculated using size conversion factors from the AAPM report 293 has the highest accuracy for estimating eye lens radiation doses ( 16 ).…”
Section: Introductionmentioning
confidence: 99%
“…With local CTDIvol, local SSDE values can be obtained. With the local SSDE value, the organ estimation becomes more accurate [22]. However, this approach alone is not sufficient to accurately estimate organ doses.…”
Section: Profiles Of Tube Current and Ctdivol In Eight Ct Scannersmentioning
confidence: 99%